PENGARUH KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PEGAWAI KEMENKUNHAM LAPAS MUARO PADANG - Yusnaena Sisca Andayani (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
The research was carried out, the Ministry of Justice and Human Rights Unit of theRegional Office Papers Prison Class IIA West Sumatra Jl. Muaro No. 42 Padang. Thephenomenon that is found in these establishments are several employees, who simply dotheir job accordingly not optimal. Based on the above background, the authors areinterested in doing more research on